Penerapan Metode Simple Additive Weighting (SAW) Dalam Menentukan Lokasi Usaha - Wati, Embun Fajar (STIKOM Tunas Bangsa Pematangsiantar, 2021)
For an entrepreneur, choosing a strategic business location is one of the main keys in establishing a business. In determining the location to choose, there are several considerations or criteria. This criterion will be the basis for choosing a location, and of course in choosing a location takes a long time because the criteria given can be very diverse. To be more effective and efficient, a Decision Support System (DSS) is needed that serves to help entrepreneurs in determining which location is most suitable. In this research the method in spk used is Simple Addidtive Weighting (SAW). SAW processes data by giving weight to the criteria used as a reference in decision making. After that, a matrix of decisions is made based on criteria. The results of the research can be the best recommendation for entrepreneurs to establish a strategic place of business in accordance with their wishes. The sequence of location selection resulting from the application of this SAW method is Teluk Naga with a final result of 6, followed by Poris with a final value of 5.66667, and lastly Dadap with a final value of 5.